Tradisi Kadeso Dalam Mempertahankan Nilai-Nilai Keagamaan di Desa Branggah Perspektif Hukum Islam - Sa'dia, Halimatus; Romli, Ahmad Syaifuddin (Maqasid: Jurnal Studi Hukum Islam, 2024)
Abstract: The Kadeso tradition in Branggah Village is a cultural ritual as an expression of gratitude to God. This study analyzes the implementation of this tradition from the perspective of Islamic law. Using a qualitative approach, data was collected through observation, interviews with religious leaders, and literature review. The results show that this tradition embodies positive values, such as gratitude and social ties, in accordance with Islamic teachings. However, some elements, such as offerings, need to be re-evaluated as they may contradict the concept of tawhid. This tradition can be maintained as long as it aligns with sharia, avoiding practices that lead to shirk. In conclusion, the Kadeso tradition remains relevant if practiced with the principles of Islamic faith, preserving culture while upholding religious teachings. Keywords: Kadeso tradition, religious values, Islamic law, gratitude, tauhid.